(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2006)
The objectives of the Land Administration Project are to increase access to land information services by all stakeholders through development of an improved land administration system in selected provinces in Vietnam. Such a system is considered to be an essential public good to be provided by the Government of Vietnam and is embedded in the government's responsibility to guide and regulate a continuation of sustainable economic and social development. There are three components to the project. The first component is the modernization of the land registration system. This component will support the development of an accurate, current and complete information system to support land registration through: (a) completing and updating all cadastral mapping showing all land parcels; (b) completing and updating all land records for land use rights and land use; (c) further developing and implementing computerized land record system; and (d) selected policy studies in support of the land administration system. The second component is the improvement of land registration service Delivery. This component will provide support for three main areas: (i) modernization and improvement of Land Registration Offices (LROs) to implement the government's policy for one door single service centers for land registration; (ii) access to land registration data through all LROs and the Internet; and (iii)comprehensive program to support public awareness raising and better communications of land registration and participation in the processes to complete and update land records, surveying and mapping. Finally, the third component will support the overall implementation of the project through project management monitoring and evaluation.
Keywords: Agriculture,Nông nghiệp